Author Correction: Evolution of host adaptation in the Salmonella typhoid toxin. (December 2017) - Gao, Xiang; Deng, Lingquan; Stack, Gabrielle; Yu, Hai; Chen, Xi; Naito-Matsui, Yuko; Varki, Ajit; Galán, Jorge
The original version of this Letter has been modified in the abstract and main text to better reflect the distribution of Neu5Ac sialoglycans in humans. Additionally, co-author Lingquan Deng's present address has been further clarified.